Skills, knowledge, and abilities of graduates from accredited environmental health science and protection undergraduate programs. - Silverman GS; Silverman MK (Journal of Environmental Health, 2003)
THE National Environmental Health Science and Protection Accreditation Council (EHAC) has the mission of enhancing the education and training of students who intend to become environmental health science and protection practitioners/professionals, Academic programs that demonstrate compliance with EHAC guidelines can become accredited with the expectation that graduates of accredited programs will have the knowledge, skills, and abilities needed for professional success. The study reported on here reviewed these guidelines in light of results from a survey of program graduates and their supervisors. The survey results were found to establish that the current approach is quite successful, and that graduates of the programs have the potential to make substantial professional contributions in protecting environmental health.